Direct gas-phase epoxidation of propylene to propylene oxide using air as oxidant on supported gold catalyst - Suo, Zhanghuai; Jin, Mingshan; Lu, Jiqing; Wei, Zhaobin; Li, Can (Journal of natural gas chemistry, 2008)
Gold catalysts supported on SiO2, TiO2, TiO2-SiO2, and ZrO2-SiO2 supports were prepared by impregnating each support with a basic solution of tetrachloroauric acid. X-ray diffraction （XRD）, transmission electron microscopy （TEM）, and X-ray photoelectron spectroscopy （XPS） techniques were used to characterize their structure and surface composition. The results indicated that the size of gold particles could be controlled to below 10 nm by this method of preparation. Washing gold catalysts with water could markedly enhance the dispersion of metallic gold particles on the surface, but it could not completely remove the chloride ions left on the surface. The catalytic performance of direct vapor-phase epoxidation of propylene using air as an oxidant over these catalysts was evaluated at atmospheric pressure. The selectivity to propylene oxide （PO） was found to vary with reaction time on the stream. At the reaction conditions of atmosphere pressure, temperature 325 ℃, feed gas ratio V（C3H6）/V（O2）= 1/2, and GHSV =6000h^-1, 17.9% PO selectivity with 0.9% propylene conversion were obtained at initial 10 min for Au/SiO2 catalyst. After reacting 60 min only 8.9% PO selectivity were detected, but the propylene conversion rises to 1.4% and the main product is transferred to acrolein （72% selectivity）. Washing Au/TiO2-SiO2 and Aa/ZrO2-SiO2 samples with magnesium citrate solution could markedly enhance the activity and PO selectivity because smaller gold particles were obtained.